(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sajan KC, Sapkota A. 2022. Additional distribution records of butterflies (Lepidoptera: Rhopalocera) with seven species new to Nepal. Biodiversitas 23: 2711-2743. New distribution records of some butterflies of Nepal are given in terms of geographical area, season and elevation based on our observations since early 2017 to late 2021. Seven new species: Hasora taminatus (Hübner, 1818), Hasora vitta (Butler, 1870), Celaenorrhinus pyrrha de Nicéville, 1889, Seseria sambara (Moore, [1866]), Coladenia agni (de Nicéville, [1884]), Erionota thrax (Linnaeus, 1767) and Tarucus balkanicus (Freyer, 1844), one new subspecies: Pelopidas conjuncta narooa (Moore, 1878) are added to the known butterfly fauna of Nepal along with two other species which need further confirmation: Rohana tonkiniana Fruhstorfer, 1906 and Neptis capnodes Fruhstorfer, 1908. Six species: Gerosis sinica (C. & R. Felder, 1862), Aeromachus kali (de Nicéville, 1885), Aeromachus pygmaeus (Fabricius, 1775), Niphanda cymbia de Nicéville, [1884], Tarucus nara (Kollar, 1848) and Discophora timora Westwood, [1850] have been reported for the second time in Nepal. This paper provides an updated distribution record of close to 200 species of butterflies in Nepal while discussing the possible causes of change in their distribution.